The ameliorative effect of gallic acid and/or Lasix on topiramate-induced renal impairment in male rats - Rana Ramadan; El-Said El-Sherbini; Gehad Elsayed; Mohamed El-Adl (Open Veterinary Journal)
Background: Topiramate (TPM) is commonly used for migraine prophylaxis; nonetheless, it is linked to nephrotoxicity, which mostly results from oxidative stress and inflammatory mechanisms.